2003
DOI: 10.3928/0148-4834-20031001-06
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Standardized Patients as a Teaching Method for Nursing Fundamentals

Abstract: This study compared two teaching methods and examined their effects on student nurses' clinical competence. A nonequivalent control group was used for this quasiexperimental research, and a posttest design was used to compare the effects on clinical competence. A protocol was developed to include critical behaviors and was used as a checklist for evaluation. The results showed that the standardized patient (SP) method was more effective than the traditional method in helping students: * Ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
1
6

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(47 citation statements)
references
References 13 publications
2
32
1
6
Order By: Relevance
“…Foi possível identificar ainda, com frequência, o uso do termo avaliação de competências para atributos de habilidades, conhecimentos e, até mesmo, de atitudes. Além disso, os instrumentos mencionados para avaliar competências, em alguns estudos, eram, na maior parte das vezes, compostos por Checklists relacionados a avaliação de habilidades e de conhecimentos [17][18][19][20][21]23,24,32,33 .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Foi possível identificar ainda, com frequência, o uso do termo avaliação de competências para atributos de habilidades, conhecimentos e, até mesmo, de atitudes. Além disso, os instrumentos mencionados para avaliar competências, em alguns estudos, eram, na maior parte das vezes, compostos por Checklists relacionados a avaliação de habilidades e de conhecimentos [17][18][19][20][21]23,24,32,33 .…”
Section: Discussionunclassified
“…São procedimentos integrantes e relevantes na formação individual dos profissionais. Muitas ações têm como base o desenvolvimento procedimental, e o sucesso de uma intervenção depende da destreza técnica na realização desses procedimentos 17,21,22,24,28,32,33 .…”
Section: Discussionunclassified
“…Advantages associated with 'live Sim' simulation training include the capacity of the virtual actor as simulated patient to reproduce a standardised persona, with whom the student interacts, with the opportunity for feedback and correction of ineffective communication (Nestel, Muir, Plant, Kidd & Thurlow 2002;Yoo & Yoo 2003;Rosenzweig, Clifton & Arnold 2007) without the undesirable artifi ciality and the potential lack of engagement that accompanies ordinary student role play.…”
Section: Using Avatars To Enhance Therapeutic Communication: Is This mentioning
confidence: 99%
“…It is well known that use of task trainers for practicing skills facilitates skill competency (Issenberg et al, 2005). However, repetitive practice, with static mannequins and task trainers, does not provide the opportunity for students to learn to perform those skills in the context of a nurse-patient relationship (Yoo & Yoo, 2003). As Yoo and Yoo (2003) noted, incorporation of psychomotor skills into HPS provides opportunity for students to perform skills as they interact with a patient or learn to adapt the skills as required for individual patient situations.…”
Section: Research On Simulation In Nursing Educationmentioning
confidence: 99%
“…Although statistically significant gains in knowledge and skill acquisition were found between pretest and posttest scores of both groups, Jeffries et al found no significant differences between the groups. Yoo and Yoo (2003) compared the effectiveness of standardized patients as a method for teaching fundamental skills. The control group, students enrolled in the nursing fundamentals course, received the traditional method of lecture, demonstration, and practice on static mannequins in the laboratory for learning basic skills.…”
Section: Research On Simulation In Nursing Educationmentioning
confidence: 99%